Wakaf Uang Terhadap Program Pengetasan Kemiskinan di Kota Metro - Tri Wahyuni, M.H (Al Qadhi Journal of Islamic Family Law, 2019)
Abstract In the provisions of the law there are two models of money waqf, namely waqf money for a certain period of time and endowments of money forever. A certain period of money waqf must be invested in banking products to make it safer and easier for the waqf party to receive the money back at maturity. While endowments of money are forever, na-zir has full authority to manage and develop waqf money to achieve the goals of their waqf. If investment activities use waqf collection funds, then for the net business profits of this investment (ie gross income minus operating costs), it will be distributed in accordance with the provisions of the waqf law, namely 90% of the profits will be intended for endowments (mauquf 'alaih) and 10% for manager or offline receipts. The managed money waqf can have a multiplier effect on the economy of Metro City, both the results of waqf investment are given in the form of economic sector assistance and non-economic sectors. These results will directly and indirectly be able to provide a significant influence in alleviating poverty. The Metro Waqf Movement is a voluntary movement that invites all campus residents to move together. Cash Waqf is a waqf mechanism for building the endowment of the ummah. By representing once but reward without stopping. In contrast to alms which are once used up, cash waqf can be developed into business units and the results are for the benefit of the ummah. So far, cash waqf has been carried out by IAIN Metro lecturers and employees voluntarily. We do cash waqf by setting aside monthly salary according to willingness. We are optimistic that this voluntary movement will increasingly invite other people to get involved without coercion. For this reason, socialization of waqf money must be continuously campaigned by all parties, especially on the Agus Salim Metro IAI Campus.